The Rise and Fall of the Iraqi Sunni Awakening Movement - Ramiz Sevdimaliyev (Vestnik MGIMO-Universiteta)
The article studies the rise of the Sunni Awakening (or Sahwa) movement as an example of how different groups can be mobilized for collective action and disintegrated by internal and external factors. It also examines the motives of the Sunni tribal leaders to oppose the AQI and the factors that had a decisive influence on the disintegration of the Awakening movement. The emergence of the Iraqi Sunni Awakening was associated not so much with a sense of ideological, patriotic, or religious obligation but with the loss of economic power of the tribal leaders who decided to mobilize against the AQI.Since 2006, the Sunni Awakening has been a key component of the US strategy to combat jihadi groups. The growth of the movement's activity led to a weakening of the Islamic State of Iraq (ISI) and a significant decrease in the intensity of interfaith conflict in the country. After the official transfer of control of the Awakening to the Iraqi government, the relationship of the Sunni tribes with official Baghdad deteriorated, as Prime Minister Al-Maliki pursued a systematic policy of marginalizing and eliminating the Awakening. The disintegration of the Awakening was strongly influenced by two US decisions that were of strategic importance to Iraq: (a) support for al-Maliki following his defeat in the 2010 parliamentary elections, won by the secular Sunni-Shiite coalition; (b) poor timing of the withdrawal of American troops from Iraq, as by the end of 2011, the Iraqi security forces were still not ready to ensure the country's security. As a result, in 2012, numerous supporters of the Sahwa began to participate in anti-government revolts, and thousands of fighters from the movement joined ISIL.